Please touch: how your sense of touch can influence marketing decisions - Peck, Joann (Henry Stewart Talks, 2013)
Haptics, Sensory, Touch, Consumer behavior, Perceived ownership, Psychological ownership, Products that encourage touch, Individual differences in touch, Product category differences in touch, Situational differences and touch, Online shopping, Motivation to touch